Developing ways of implementing biocatalytic hydrogenation reactions in flow - Poznansky, B (2021)
The use of enzymes as catalysts is becoming more common, in part due to their high selectivity under mild reaction conditions. However, many redox enzymes require cofactors (NADH or NADPH) as an electron source to operate.Due to the high cost of NAD(P)H, cofactor regeneration systems have been developed, which often involve addition of a second enzyme and/or a sacrificial reductant. Furthermore, the enzymes can be difficult to recover from solution, which can inhibit the uptake of biocatalytic processes. Immobilising enzymes on a support allows for easier recovery and re-use of the biocatalyst, lowering the cost of the process, however, no enzyme immobilisation system has found ubiquity.Flow chemistry is a technique that has seen an increase in research and industrial implementation in recent years, for its greener and more efficient chemical production.Supported biocatalysts are suited to use in flow reactors, where the catalyst is retained within the reactor and substrates are continuously pumped through.The work in this Thesis seeks to address the challenges associated with using immobilised redox enzymes for chemical synthesis in continuous flow. First, the translation of industry standard cofactor recycling systems (FDH–formate and ADH–IPA) onto a simple carbon particle support and into flow was studied. The continuous synthesis of industrially relevant enantiomerically pure molecules was demonstrated for both systems. Next, work focused on translating aH2-driven cofactor recycling system into continuous flow. The H2-driven ‘HydRegen’ system uses a robust hydrogenase and NAD+ reductase immobilised onto an electron conducting carbon support to regenerate NADH. Application of the H2-driven cofactor regeneration system in a commercially available hydrogenation flow reactor demonstrated high turnover frequencies of 85,200 h−1 and the production of an industrially relevant molecule.